Training cognition : optimizing efficiency, durability, and generalizability - Healy, Alice F.; Bourne, Lyle Eugene, 1932- (New York, NY : Psychology Press, 2012)
'This book describes research on training using cognitive psychology to build a complete empirical and theoretical picture of the training process. It includes a review of relevant cognitive psychological literature, a summary of recent laboratory experiments, a presentation of original theoretical ideas, and a discussion of possible applications to real-world training settings'--Provided by publisher.
Introduction : Training MURI project / Alice F. Healy and Lyle E. Bourne Jr. -- Empirically valid principles of training / Alice F. Healy, Vivian I. Schneider, and Lyle E. Bourne Jr. -- Basic research on training principles / Alice F. Healy, Lyle E. Bourne Jr., and other members of the Healy-Bourne laboratory -- Role of attention in training / Christopher D. Wickens -- Training and transfer of basic components of skill / Robert W. Proctor, Motonori Yamaguchi, and James Miles -- Automation and effective training / Benjamin Clegg and Eric Heggestad -- Impact of Technology on Training / Stephen Goldberg and Paula Durlach -- Training Taxonomy : Tasks, methods, and performance measures / William D. Raymond, Alice F. Healy, and Lyle E. Bourne Jr. -- Instance-based models of training / Cleotilde Gonzalez -- Component-process models of training / Carolyn J. Buck-Gengler -- Training models : Comparison, evaluation, and optimization / Bengt Fornberg and William D. Raymond -- Over-arching quantitative framework of training / Matt Jones ... [et al.] -- Principles applicable to education and training / Mark A. McDaniel -- Training for the real world / Immanuel Barshi, Loukia Loukopoulos, and Key Dismukes -- Conclusions : Current status of knowledge about training / Lyle E. Bourne Jr. & Alice F. Healy.
Keywords: Cognitive styles; Employees -- Training of